2010
DOI: 10.1001/archinternmed.2009.536
|View full text |Cite
|
Sign up to set email alerts
|

Standard Care Impact on Effects of Highly Active Antiretroviral Therapy Adherence Interventions

Abstract: Intervention and control patients were exposed to effective adherence care. Future meta-analyses of (behavior change) interventions should control for variability in care delivered to active controls. Clinical practice may be best served by implementing current best practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
182
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(190 citation statements)
references
References 69 publications
6
182
1
1
Order By: Relevance
“…Both Ayling, Brierley, Johnson, Heller, and Eiser (2015) and Bishop, Fenge-Davies, Kirby, and Geraghty (2015) examine the role of the support provided to control groups in HBC trials. Previous studies suggested that the active content of support provided to control groups in HBC trials may vary considerably between studies, impact control group success rates and -consequently -trial effect sizes (de Bruin, Viechtbauer, Hospers, Schaalma, & Kok, 2009;de Bruin et al, 2010). Ayling and colleagues examine this issue in trials promoting self-management among young people with type 1 diabetes.…”
Section: The Articles In This Special Issuementioning
confidence: 99%
“…Both Ayling, Brierley, Johnson, Heller, and Eiser (2015) and Bishop, Fenge-Davies, Kirby, and Geraghty (2015) examine the role of the support provided to control groups in HBC trials. Previous studies suggested that the active content of support provided to control groups in HBC trials may vary considerably between studies, impact control group success rates and -consequently -trial effect sizes (de Bruin, Viechtbauer, Hospers, Schaalma, & Kok, 2009;de Bruin et al, 2010). Ayling and colleagues examine this issue in trials promoting self-management among young people with type 1 diabetes.…”
Section: The Articles In This Special Issuementioning
confidence: 99%
“…The intervention, which included motivational interviewing as a core element and included a combination of related and supplementary behavior change techniques [28], was compared with standard care [29] in a randomized controlled trial design. We hypothesized that the active multicomponent intervention would lead to better medication adherence compared with standard care at the follow-up measurement points 3 and 6 months following delivery of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…There is a recognised need to specify interventions in greater detail and with more consistent terminology and for evaluation studies to specify the components of the interventions in both the experimental and control groups [17][18][19][20][21]. In order to create a standardised vocabulary with which researchers and others can define and describe intervention components (i.e.…”
Section: Behaviour Change Techniques: the Components Of Behaviour Chamentioning
confidence: 99%